Liquid chromatographic methods for the determination of direct oral anticoagulant drugs in biological samples: A critical review - Gouveia, Filipa Fontoura Diogo Henriques de (2019)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia